Fabrication and evaluation of some electrochemical properties of screen-printed electrodes for use in electrochemical analysis - Hoang, Thai Long; Phan, Trung Ngoc; Ho, Xuan Anh Vu; Nguyen, Dang Giang Chau; HO, Van Minh Hai (Hue University Journal of Science: Natural Science, 2024)
Three types of conductive inks, including Ceres, Acheson carbon inks, and Ag/AgCl ink, were utilized to fabricate screen-printed electrodes (SPEs) on a 0.4 mm thick polyethylene terephthalate substrate using a screen-printing technique. To enhance the electrical conductivity, the printed electrodes were cured at 80°C for 90 minutes. The basic electrochemical properties of the self-made SPEs using these conductive inks were determined, evaluated, and compared with commercial SPEs from Metrohm. Although the electroactive surface areas of the self-made SPEs were not significantly different from those of the commercial SPEs, the heterogeneous electron transfer rates on the surfaces of self-made SPEs using Ceres and Acheson inks were inferior to those of the commercial SPEs. However, after pre-condition by applying a potential of +1.2 V for 180 s in a 2 M Na2CO3 solution, the electrochemical properties of the self-made SPEs, including the active surface areas and heterogeneous electron transfer rates, were significantly improved and became better than those of the commercial SPEs.